Le Traité de Lisbonne remet-il l’Europe « sur les rails » ? - Dominique Rivière (EchoGéo)
The Treaty of Lisbon is supposed to "release" the European construction. But the crisis into which got stuck this process is linked to various scales of time and causalities, which are more or less easy to reduce. Moreover, the Treaty changes the european governance by marking a return of States and by ratifying the principle of « Europe with variable geometry ». It brings a resolution in the problem of the representation of the diversity of States, but they will have to wait for 2014 or even on 2017 for his putting into practice.